Systematic structure of the ancient settlements flora in the Lower Dnipro (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
The article provides an analysis of the systematic structure of the ancient settlements flora located in the Lower Dnipro basin (Southern Ukraine). Despite the relatively small size, the settlements are characterized by a high level of floristic richness. In 18 studied ancient settlements we recorded 524 species belonging to 281 genera, 74 families, 3 classes and 2 divisions of vasculat plants. The floristic proportion for the flora of ancient settlements is 1: 3.8: 7,1, the generic coefficient is 1.9. The spectrum of leading families of flora (61,8 % of the total species composition) reflects zonal features of the Holarctic floras. Most of them are characterized by a hight rates of the indigenous faction (74% in avarage), which indicate flora as natural. The presence of such families as Chenopodiaceae, Brassicaceae and Boraginaceae in the leading family spectrum, shows a slight shift to the arid flora of the Mediterranean. Another reason is the processes of plant invasion from neighboring agrolandscapes and the corresponding processes of synatropization. Spectrum of the leading genera of flora represented by polymorphic genuses – Veronica (13 species), Astragalus (9 species), Artemisia, Carex, Euphorbia, Galium (8 species). The complete absence of synanthropophytes within the genera Achillea, Allium, Astragalus, Carex, Dianthus, Euphorbia, Potentilla, Salvia, Verbascum is indicative. The genera Allium, Astragalus and Dianthus are fully represented by indigenophytes.
Keywords: conspectus flora, vascular plants, rare communities, steppe, the Lower Dnipro, conservation of nature.